1980
DOI: 10.1536/ihj.21.590
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Depression in Spontaneously Hypertensive Rats

Abstract: In 1963, a strain of SHR rats which developed spontaneously hypertension was isolated from Wistar rats by Okamoto and Aoki (JPN CIRC J 27: 282, 1963).In preliminary studies to investigate T-lymphocyte markers in rats we noted that SHR rats had reduced numbers of rosette forming cells in their thymuses when compared to other rat strains (CELL IMMUNOL 27: 52, 1976). Additional studies were undertaken to more clearly determine if additional impairment of immunological functions existed in this rat strain with hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 7 publications
3
41
1
Order By: Relevance
“…The concept of investigating the role of IL-2 and other immune cell modulators in the pathogenesis of hypertension is of great scientific interest and potential therapeutic usefulness, as previous studies have demonstrated that SHR have depressed T cell function and fewer thymic T cells than normotensive allogeneic strains. 4 -7 A significant reduction in blood pressure has been observed 6 -14 in SHR with established hypertension given Wistar-King-Aptekman or Wistar thymic implants. This attenuation of hypertension obtained by thymic implantation was dependent on multiple implants, and in one study, 6 this attenuation was transient.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of investigating the role of IL-2 and other immune cell modulators in the pathogenesis of hypertension is of great scientific interest and potential therapeutic usefulness, as previous studies have demonstrated that SHR have depressed T cell function and fewer thymic T cells than normotensive allogeneic strains. 4 -7 A significant reduction in blood pressure has been observed 6 -14 in SHR with established hypertension given Wistar-King-Aptekman or Wistar thymic implants. This attenuation of hypertension obtained by thymic implantation was dependent on multiple implants, and in one study, 6 this attenuation was transient.…”
Section: Discussionmentioning
confidence: 99%
“…40 Additional studies suggested that hypertension in this model was associated with altered immune reactivity, as evidence by impaired blastogenic responses and altered cellular immune reactivity. 41 Our group has hypothesized that the benefit of immunosuppression on salt sensitivity may relate in part to a direct inhibition of the inflammatory response that occurs in the kidneys in SSHTN. Indeed, we have noted a remarkable relationship between the presence of T cells and macrophages in the interstitium with salt-sensitive blood pressure in numerous models.…”
Section: Renal Microvascular Disease and Interstitial Inflammation Armentioning
confidence: 99%
“…23 Especially in the case of genetic hypertension, it has been suggested that the suppressor thymus-derived (T) lymphocyte dysfunctions and subsequent autoimmunities would bring about vascular injuries and renal damage, both of which are supposed to contribute to the development and maintenance of hypertension. 4 " 6 In fact, it has been demonstrated that the periarterial spaces are infiltrated with inflammatory cells in aged spontaneously hypertensive rats (SHR) and these lesions are resolved by immunosuppressive therapy. 7 Moreover, the arterial damage in salt-induced hypertension could not be produced in nude mice.…”
Section: S Ince White and Grollmanmentioning
confidence: 99%